Bay Cadet Tells of Tragic Train Crash - Ferris, John (Unknown)
Jerry Aspland of Pittsburg, 22-year-old California Maritime Academy midshipman, modestly described the heroic action of a group of cadets at the scene of a shattering train collision in Colombia last month.